2021
DOI: 10.1136/jmedgenet-2021-107751
|View full text |Cite
|
Sign up to set email alerts
|

De novo coding variants in the AGO1 gene cause a neurodevelopmental disorder with intellectual disability

Abstract: BackgroundHigh-impact pathogenic variants in more than a thousand genes are involved in Mendelian forms of neurodevelopmental disorders (NDD).MethodsThis study describes the molecular and clinical characterisation of 28 probands with NDD harbouring heterozygous AGO1 coding variants, occurring de novo for all those whose transmission could have been verified (26/28).ResultsA total of 15 unique variants leading to amino acid changes or deletions were identified: 12 missense variants, two in-frame deletions of on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…The AGO1 protein consists of four major domains: N‐terminal, PAZ, MID, and PIWI, as well as two linker domains. Combined with the variants of Schalk et al (2022) and the previously reported, most of the variants causing substitutions or small deletion of amino acids have clustered in the Argonaute linker‐1 and PAZ domain. By using the three‐dimensional conformation predictions, Schalk et al (2022) suggested that the variants could result in the functional alteration of AGO1, leading to dysfunction in RNA processing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The AGO1 protein consists of four major domains: N‐terminal, PAZ, MID, and PIWI, as well as two linker domains. Combined with the variants of Schalk et al (2022) and the previously reported, most of the variants causing substitutions or small deletion of amino acids have clustered in the Argonaute linker‐1 and PAZ domain. By using the three‐dimensional conformation predictions, Schalk et al (2022) suggested that the variants could result in the functional alteration of AGO1, leading to dysfunction in RNA processing.…”
Section: Discussionmentioning
confidence: 67%
“…In humans, there are four AGO proteins, of which the best known, AGO1, interacts with RNA Pol II and the regulatory elements of gene expression (Alló et al, 2014). Recently, AGO1 pathogenic variants and gross deletions encompassing AGO1 have been shown to link to neurodevelopmental disorders in humans (Rauch et al, 2012; Sanders et al, 2012; Hamdan et al, 2014; Iossifov et al, 2014; Tokita et al, 2015; Kosmicki et al, 2017; Martínez et al, 2017; Turner et al, 2017; Sakaguchi et al, 2019; Takata et al, 2018; Turner et al, 2019; Edwards et al, 2020; Klee et al, 2021; Schalk et al, 2022; Niu et al, 2022). However, clinical reports of CHD associated with the AGO1 variant have been limited (Edwards et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The pLi score of AGO1 , provided in the gnomAD database, is 1, suggesting that haploinsufficiency is likely to be the main disease driver. De novo missense variants have been reported in AGO1 in individuals with a broad spectrum of NDDs, including global DD, ID, autism spectrum disorder (ASD), hypotonia, dysmorphism, behavioral features, and language impairment with or without epilepsy [ 49 , 50 , 51 , 52 ]. The reported variants of AGO1 gene are mainly nucleotide changes, while in our patient, a deletion including the first eight exons of the transcript was revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Whole‐exome sequencing was performed on patient‐parent trios using published procedures 5, 7 . Rare‐variant interrogation was first done with virtual panels containing genes with described association with monogenic disorders to exclude known disease etiologies 5, 7 . New candidates were ranked based on established criteria 5, 7 .…”
Section: Methodsmentioning
confidence: 99%